Characterizing high-burden rosacea subjects: a multivariate risk factor analysis from a global survey. (17th February 2020) - Tan, Jerry; Steinhoff, Martin; Bewley, Anthony; Gieler, Uwe; Rives, Vincent
Abstract: Objective: To characterize rosacea features suitable for identification of high-burden (HB) subjects in clinical practice. Design: Global online survey with subjects recruited using an online panel from the United States, Canada, Italy, United Kingdom, Germany and France. Subjects self-reported a physician's diagnosis of rosacea. Measurements: HB subjects were defined as those with ≥3/4 domains (quality of life, lifestyle adaptation, time trade-off, willingness to pay) greater than the median. Group characteristics were analyzed and multivariate-logistic modeling used to investigate factors most associated with HB. Results: 710 subjects completed the survey, including 158 HB subjects. HB was observed in all self-declared rosacea severities. HB subjects were more likely to spend more time daily on skin care and experienced approximately double the impact of health problems on work productivity in the past 7 days ( p  < .01). In the past 12 months, HB subjects were more likely to have at least one visit to the emergency room (41.8% vs 11.2%; p  < .01). In the multivariate risk analysis, factors most associated with HB included rosacea severity, impact of health problems on regular daily activities and age at first symptoms. Conclusion: Rosacea has a distinct subset of HB subjects who can be successfully characterized.